EVALUASI TINGKAT PENERIMAAN E-MONEY DI KALANGAN MAHASISWA YOGYAKARTA MENGGUNAKAN MODIFIKASI UTAUT2 - Evan, Irfan; Winarno, Wing Wahyu; Putro, Hanson Prihantoro (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.01.TAHUN. 2021, 2021)
In recent years, electronic money has received public attention as an alternative payment system in Indonesia. Based on data from Bank Indonesia, the volume and value of electronic money transactions has grown significantly in the last 10 years. But in reality, the number of users is still small when compared to debit cards. Many factors cause people to be reluctant to use e-money as a method of electronic transactions. Therefore, this study will evaluate the acceptance rate of electronic money among students and the factors that affect its acceptance. This study uses UTAUT2 which can add Trust, Perceived Risk and Perceived Security variables. Data was collected through distributing questionnaires online using google forms to 180 users. The data analysis method in this study used multiple linear regression and used SPSS software. The result, the level of acceptance of e-money among students is in a good category. It is known, Behavior Intention positively by Perceived Security, Price Value, Habit, Performance Expectancy, Trust, Facilitating Condition, Hedonic Motivation and negatively by Perceived Risk but not by Effort Expectancy and Social Influence.